Conceptual masking disrupts change-detection performance. - Blalock, Lisa Durrance; Weichman, Kyle; VanWormer, Lisa A. (Memory & Cognition, 2024)
The present study investigated the effects of long-term knowledge on backward masking interference in visual working memory (VWM) by varying the similarity of mask stimuli along categorical dimensions. To-be-remembered items and masks were taken from categories controlled for perceptual distinctiveness and distinctiveness in kinds (e.g., there are many kinds of cars and few kinds of coffee mugs). Participants completed a change-detection task in which the memory array consisted of exemplars from either a similar or distinctive category, followed by a mask array of items from the same category (conceptually similar versus conceptually distinct categories), a different category, or no mask. The results over two experiments showed greater interference from conceptually similar masks as compared with the other conditions across stimulus onset asynchrony (SOA) conditions, suggesting masking with conceptually similar categories leads to more interference even when masks are shown well after the stimulus. These results have important implications for both the nature and time course of long-term conceptual knowledge influencing VWM, particularly when using complex real-world objects.